Axonal and astrocyte injury markers in the cerebrospinal fluid of Kenyan children with severe malaria. - Medana, I; Idro, R; Newton, C (2007)
A retrospective study of cerebrospinal fluid (CSF) levels of markers of brain parenchymal damage was conducted in Kenyan children with severe falciparum malaria. Two markers were analysed by immunoassays: the microtubule-associated protein tau for degenerated axons and S-100B for astrocytes. The level of tau proteins in the CSF was significantly elevated in children with cerebral malaria compared with either malaria with prostration or malaria with seizures but normal consciousness (p<0.001). Elevated tau was also found to be associated with impaired delivery of oxygen (severe anaemia), severe metabolic acidosis manifesting as respiratory distress (increased respiratory rate and deep acidotic breathing) and at higher parasite densities. Elevated S-100B in children was associated with an increased risk of repeated seizures. This study provides evidence that axonal injury is associated with malaria coma and identifies the potential role of severe anaemia, acidosis and hyperparasitaemia to causing brain parenchymal damage in children with malaria.